Photosensitive resin composition, photosensitive resin film, multilayer printed wiring board, semiconductor package, and method for producing multilayer printed wiring board
By adding specific inorganic filler materials and photopolymerizable compounds to the photosensitive resin composition, the through holes are formed by combining photolithography, the problems of dielectric constant and bonding strength in the 10GHz frequency band are solved, and the manufacturing efficiency of printed wiring boards is improved. quality.
Patent Information
- Application Number
- CN202380037457.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-08
- Publication Date
- 2024-12-31
AI Technical Summary
The prior art is difficult to take into account the relative dielectric constant and the bonding strength of the copper plating layer in the 10GHz frequency band, and the laser processing through-hole formation efficiency is low, which affects the manufacturing efficiency.
A photosensitive resin composition containing an inorganic filler material with a true density of less than or equal to 1,500 kg/m3 is used to form through holes by photolithography, and a specific photopolymerizable compound and a thermosetting resin are added to the resin composition to improve the bonding strength. and dielectric constant.
It achieves excellent relative dielectric constant and high bonding strength in the 10GHz frequency band, and improves the manufacturing efficiency and quality of multi-layer printed wiring boards.
Smart Images

Figure CN119234184A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a photosensitive resin composition, a photosensitive resin film, a multilayer printed wiring board and a semiconductor package, and a method for producing the multilayer printed wiring board. Background Art
[0002] In recent years, electronic devices have been miniaturized and improved in performance, and multilayer printed wiring boards have been increasingly densified due to the increase in the number of circuit layers and the miniaturization of wiring. In particular, semiconductor package substrates such as BGA (ball grid array) and CSP (chip size package) equipped with semiconductor chips have become more dense, requiring not only miniaturization of wiring but also thinning of insulating layers and further reduction in diameter of through holes (also called via holes) for interlayer connections.
[0003] As a conventional method for manufacturing a printed wiring board, there is a method for manufacturing a multilayer printed wiring board based on a build-up method in which an interlayer insulating layer and a conductor circuit layer are sequentially stacked (for example, see Patent Document 1). In a multilayer printed wiring board, as circuits become smaller, a semi-additive method in which circuits are formed by plating has become the mainstream.
[0004] In the conventional semi-additive method, for example, (1) a thermosetting resin film is laminated on a conductor circuit and then cured by heating to form an "interlayer insulating layer". (2) Then, after forming through holes for interlayer connection by laser processing, desmearing and roughening are performed by alkaline permanganate treatment or the like. (3) Then, the substrate is subjected to electroless copper plating, a pattern is formed using a resist, and then copper is electroplated to form a copper circuit layer. (4) Then, after stripping the resist, flash etching of the chemically plated layer is performed to form a copper circuit.
[0005] As described above, laser processing has become the mainstream method for forming through holes in an interlayer insulating layer formed by curing a thermosetting resin film, but the reduction in diameter of through holes achieved by laser irradiation using a laser processing machine is reaching its limit. Furthermore, in the formation of through holes using a laser processing machine, each through hole needs to be formed one by one. In the case where a plurality of through holes need to be provided due to high density, the formation of the through holes requires a lot of time, resulting in a problem of poor manufacturing efficiency.
[0006] Under such circumstances, as a method capable of forming multiple through holes at a time, the following method has been proposed: using a photosensitive resin composition containing an acid-modified vinyl epoxy resin, a photopolymerizable compound, a photopolymerization initiator, an inorganic filler and a silane compound, and wherein the content of the inorganic filler is 10 to 80% by weight, a plurality of small-diameter through holes are formed at a time by photolithography (for example, refer to Patent Document 2).
[0007] In Patent Document 2, one of the problems is to suppress the reduction in adhesion to the copper plating layer caused by using a photosensitive resin composition instead of a conventional thermosetting resin composition as a material for an interlayer insulating layer or a surface protective layer, and further, these problems are solved based on the resolution of through holes and the adhesion with a silicon raw material substrate and chip components.
[0008] In recent years, substrate materials are required to be applied to fifth-generation mobile communication system (5G) antennas using high-frequency band radio waves and millimeter-wave radars using higher-frequency band radio waves. Therefore, as one of the goals, it is necessary to develop a resin composition with a further improved relative dielectric constant in the "10 GHz band". However, in the technology of Patent Document 2, there is room for improvement in the relative dielectric constant in the 10 GHz band.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Laid-Open No. 7-304931
[0012] Patent Document 2: Japanese Patent Application Publication No. 2017-116652 Summary of the invention
[0013] Problems to be solved by the invention
[0014] The inventors of the present invention studied the inclusion of polytetrafluoroethylene (hereinafter referred to as PTFE) particles having a very low relative dielectric constant in a photosensitive resin composition in order to reduce the relative dielectric constant in the 10 GHz frequency band. However, when only PTFE is included in the photosensitive resin composition, although the relative dielectric constant can be reduced, the problem of reduced bonding strength with the copper plating layer arises, and it is found that it is difficult to take into account both the relative dielectric constant in the 10 GHz frequency band and the bonding strength with the copper plating layer.
[0015] Therefore, the object of the present disclosure is to provide a photosensitive resin composition that exhibits an excellent relative dielectric constant in a 10 GHz frequency band and high bonding strength with a copper plating layer, and a photosensitive resin film formed using the photosensitive resin composition, and to provide a multilayer printed wiring board and a method for producing the same, and a semiconductor package.
[0016] Means for solving problems
[0017] The present inventors have conducted intensive studies and have found that the above-mentioned object can be achieved by the present disclosure.
[0018] The present disclosure includes the following embodiments [1] to
[18] .
[0019] [1] A photosensitive resin composition comprising (X) as a photosensitive resin composition having a true density of less than or equal to 1,500 kg / m 3 Inorganic filling material with solid particles.
[0020] [2] The photosensitive resin composition according to [1] above, wherein the component (X) has a volume average particle size of 0.3 to 3 μm.
[0021] [3] The photosensitive resin composition according to [1] or [2], wherein the content of the component (X) is 1 to 45% by volume based on the total solid content of the photosensitive resin composition.
[0022] [4] The photosensitive resin composition according to any one of [1] to [3] above, further comprising (A) a photopolymerizable compound having an ethylenically unsaturated group and an acidic substituent and (B) a thermosetting resin.
[0023] [5] The photosensitive resin composition according to [4], wherein the component (A) comprises an alicyclic skeleton represented by the following general formula (A-1).
[0024] [Chemistry 1]
[0025]
[0026] (Where R A1 represents an alkyl group having 1 to 12 carbon atoms, which may be substituted at any position of the above-mentioned alicyclic skeleton. 1 is an integer from 0 to 6. * is a bonding site with other structures. )
[0027] [6] The photosensitive resin composition according to [4] or [5], wherein the equivalent ratio of the acidic substituent of the component (A) to the epoxy group of the component (B) [epoxy group / acidic substituent] is 0.5 to 6.0.
[0028] [7] The photosensitive resin composition according to any one of [1] to [6] above, further comprising (C) a crosslinking agent.
[0029] [8] The photosensitive resin composition according to any one of [1] to [7] above, further comprising (D) an elastomer.
[0030] [9] The photosensitive resin composition according to any one of [1] to [8] above, further comprising (E) an organic filler.
[0031]
[10] The photosensitive resin composition according to [9] above, wherein the component (E) comprises resin particles composed of at least one selected from the group consisting of a resin having a fluorine atom, polyethylene, polypropylene, polystyrene, polyphenylene ether and silicone.
[0032]
[11] The photosensitive resin composition according to [9] or
[10] , wherein the content of the component (E) is 1 to 45% by volume based on the total solid content of the photosensitive resin composition.
[0033]
[12] The photosensitive resin composition according to any one of [1] to
[11] , further comprising (H) a photopolymerization initiator.
[0034]
[13] The photosensitive resin composition according to
[12] above, comprising two or more of the above-mentioned components (H).
[0035]
[14] A photosensitive resin composition for forming an optical via hole, comprising the photosensitive resin composition according to any one of [1] to
[13] .
[0036]
[15] A photosensitive resin film formed using the photosensitive resin composition according to any one of [1] to
[13] above.
[0037]
[16] A multilayer printed wiring board comprising an interlayer insulating layer formed using the photosensitive resin composition according to any one of [1] to
[13] or the photosensitive resin film according to
[15] .
[0038]
[17] A semiconductor package comprising the multilayer printed wiring board according to
[16] above, and a semiconductor element.
[0039]
[18] A method for manufacturing a multilayer printed wiring board, comprising the following (1), (2) and (4).
[0040] (1): The photosensitive resin film described in
[15] above is laminated on one or both surfaces of a circuit board.
[0041] (2): The photosensitive resin film laminated in the above (1) is exposed and developed to form an interlayer insulating layer having a through hole.
[0042] (4): A circuit pattern is formed on the above-mentioned interlayer insulating layer.
[0043] Effects of the Invention
[0044] According to the present disclosure, a photosensitive resin composition showing excellent relative dielectric constant at 10 GHz frequency band and high bonding strength with copper plating can be provided. In addition, a photosensitive resin film formed using the photosensitive resin composition can be provided. Moreover, a multilayer printed wiring board containing an interlayer insulating layer formed using the photosensitive resin composition or the photosensitive resin film can be provided, and a method for manufacturing the multilayer printed wiring board can also be provided. In addition, a semiconductor package comprising the multilayer printed wiring board and a semiconductor element can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] [ Figure 1 ] is a schematic diagram showing one method of manufacturing a multilayer printed wiring board using the photosensitive resin film of the present embodiment as a material for at least one of a surface protective layer and an interlayer insulating layer. DETAILED DESCRIPTION
[0046] In the numerical range described in this specification, the upper limit or lower limit of the numerical range can be replaced by the value shown in the embodiment. In addition, the lower limit and upper limit of the numerical range can be arbitrarily combined with the lower limit or upper limit of other numerical ranges. In the expression of the numerical range "AA to BB", the numerical values AA and BB at both ends are included in the numerical range as the lower limit and upper limit, respectively.
[0047] In this specification, for example, a statement such as "greater than or equal to 10" refers to 10 and a value greater than 10, and this is also used as a reference when the values are different. In addition, for example, a statement such as "less than or equal to 10" refers to 10 and a value less than 10, and this is also used as a reference when the values are different.
[0048] In this specification, when there are plural kinds of substances corresponding to the components, the content of each component in the photosensitive resin composition refers to the total content of the plural kinds of substances present in the photosensitive resin composition unless otherwise specified.
[0049] In the present specification, the "ring carbon number" refers to the number of carbon atoms required to form a ring, and does not include the number of carbon atoms of substituents possessed by the ring. For example, the number of ring carbon atoms of a cyclohexane skeleton and a methylcyclohexane skeleton are both 6.
[0050] The expression "(meth)acrylic acid XX" means one or both of acrylic acid XX and the corresponding methacrylic acid XX. In addition, "(meth)acryloyl" means one or both of acryloyl and methacryloyl.
[0051] In this specification, “relative dielectric constant” refers to the relative dielectric constant in a 10 GHz frequency band unless otherwise specified.
[0052] Furthermore, any combination of the matters described in this specification is also included in this embodiment.
[0053] [Photosensitive resin composition]
[0054] A photosensitive resin composition according to one embodiment of the present disclosure (hereinafter, sometimes simply referred to as the present embodiment) contains (X) as a true density of 1,500 kg / m or less. 3A photosensitive resin composition containing an inorganic filler material having solid particles.
[0055] Here, in this specification, the above-mentioned component may be simply referred to as "component (X)", and the same abbreviation may be applied to other components.
[0056] It should be noted that in this specification, "resin component" refers to the components (A) and (B) described later, and also includes other components that may be contained as needed (such as components (C), (D), (E), (F), (G), (H) and (I), but does not include component (X), other inorganic fillers and inorganic compounds such as pigments. In addition, "solid content" refers to non-volatile components other than water contained in the photosensitive resin composition and the diluent described later, and also includes substances that are liquid, syrupy and waxy at room temperature around 25°C.
[0057] The photosensitive resin composition of the present embodiment has an excellent relative dielectric constant at a frequency band of 10 GHz and is suitable for through-hole formation (also referred to as optical through-hole formation) by photolithography, and is therefore suitable for forming one or more selected from the group consisting of optical through-holes and interlayer insulating layers. Here, in the present disclosure, when a "layer" is expressed as an interlayer insulating layer, in addition to a solid layer, a layer in which at least a portion of the layer is not a solid layer but is island-shaped, a layer in which a hole is formed, and a layer in which the interface with the adjacent layer becomes unclear are also included in the "layer". In addition, the solid layer refers to a sheet-like layer that is not specially processed.
[0058] In addition, the photosensitive resin composition of this embodiment is suitable for a negative photosensitive resin composition.
[0059] Hereinafter, after describing the component (X) in detail, each other component which the photosensitive resin composition of this embodiment may contain will be described in detail.
[0060] <(X) as true density less than or equal to 1,500kg / m 3 Solid particles of inorganic filler materials>
[0061] The photosensitive resin composition of the present embodiment contains a true density of 1,500 kg / m or less. 3The inorganic filler material of the solid particles is used as the (X) component, thereby showing an excellent relative dielectric constant under the 10GHz frequency band and a high bonding strength with the copper plating layer. Here, the true density of the (X) component is a value measured by a dry automatic density meter "AccuPycII 1340" (manufactured by Shimadzu Corporation), and more specifically, a value measured by the method described in the embodiments. In addition, in the present disclosure, "solid particles" refer to particles whose hollowness obtained by the true density measured by a dry automatic density meter (specifically, the method described in the embodiments) is less than or equal to 60% (including 0%, i.e., 0 to 60%), and when the hollowness measured by the method is greater than 60%, it is called a "hollow particle". Therefore, for example, even if the inside of the particle is porous, as long as the above-mentioned hollowness is less than or equal to 60%, it is also included in the solid particles.
[0062] From the viewpoint of relative dielectric constant and bonding strength with copper plating, the above-mentioned hollow ratio of solid particles is preferably less than or equal to 55%, more preferably less than or equal to 50%, further preferably less than or equal to 45%, and particularly preferably less than or equal to 43%. The lower limit of the above-mentioned hollow ratio is not particularly limited, and may be greater than or equal to 0%, greater than or equal to 5%, greater than or equal to 15%, greater than or equal to 25%, greater than or equal to 30%, greater than or equal to 32%, greater than or equal to 34%, or greater than or equal to 37%. It should be noted that the method for obtaining the above-mentioned hollow ratio is as described in the examples.
[0063] The exact mechanism of excellent relative dielectric constant and high bonding strength with copper plating is not clear, but it is speculated that: 3 , as the space on the molecular level of the inorganic filler material of solid particles becomes larger, which may be related to the reduction of relative dielectric constant. In addition, it is believed that since the (X) component is an inorganic filler material, the bond strength with the copper coating will not be greatly reduced as PTFE, so the reduction of relative dielectric constant and the high bond strength with the copper coating can be taken into account. However, the scope of the photosensitive resin composition of the present embodiment is not limited by this speculation.
[0064] From the viewpoint of relative dielectric constant and bonding strength with the copper plating layer, the true density of the component (X) is preferably 1,000 to 1,500 kg / m 3 , more preferably 1,100 to 1,500 kg / m 3 , more preferably 1,200 to 1,500 kg / m 3 , particularly preferably 1,250 to 1,450 kg / m 3 , most preferably 1,250 to 1,400 kg / m 3 .
[0065] Component (X) includes silicon dioxide (SiO2), aluminum oxide (Al2O3), titanium dioxide (TiO2), tantalum oxide (Ta2O5), zirconium oxide (ZrO2), silicon nitride (Si3N4), barium titanate (BaO·TiO2), barium carbonate (BaCO3), magnesium carbonate (MgCO3), aluminum hydroxide (Al(OH)3), magnesium hydroxide (Mg(OH)2), lead titanate (PbO·TiO2), lead zirconate titanate (PZT), lead lanthanum zirconate titanate (PLZT), gallium oxide (Ga2O3), spinel (MgO·Al2 O3), mullite (3Al2O3·2SiO2), cordierite (2MgO·2Al2O3 / 5SiO2), talc (3MgO·4SiO2·H2O), aluminum titanate (TiO2·Al2O3), zirconium oxide containing yttria (Y2O3·ZrO2), barium silicate (BaO·8SiO2), boron nitride (BN), calcium carbonate (CaCO3), barium sulfate (BaSO4), calcium sulfate (CaSO4), zinc oxide (ZnO), magnesium titanate (MgO·TiO2), hydrotalcite, mica, calcined kaolin, carbon (C), etc. Among them, silicon dioxide is preferred from the viewpoint of heat resistance, low thermal expansion and relative dielectric constant.
[0066] As the component (X), a commercially available product can be used. For example, a product with a true density of less than or equal to 1,500 kg / m 3 Solid particle silica includes "BQQ-0710SCB" (manufactured by TAT) and "BQQ-0310SCB" (manufactured by TAT). The true density is less than or equal to 1,500 kg / m 3 The silicon dioxide of the solid particles is not particularly limited, but preferably has Si-R in addition to Si-O bonds. X Key (R X represents an organic group).
[0067] From the viewpoint of improving the dispersibility in the photosensitive resin composition, the component (X) may be a component that has been surface-treated with a coupling agent or a component that has not been surface-treated with a coupling agent, and is preferably a component that has been surface-treated with a coupling agent. Examples of the coupling agent include aminosilane coupling agents, epoxysilane coupling agents, phenylsilane coupling agents, alkylsilane coupling agents, alkenylsilane coupling agents, alkynylsilane coupling agents, haloalkylsilane coupling agents, siloxane coupling agents, hydrogensilane coupling agents, silazane coupling agents, alkoxysilane coupling agents, chlorosilane coupling agents, (meth)acrylic silane coupling agents, isocyanurate silane coupling agents, urea silane coupling agents, mercaptosilane coupling agents, sulfide silane coupling agents, and isocyanate silane coupling agents.
[0068] The volume average particle size of the component (X) is preferably 0.3 to 3 μm, more preferably 0.3 to 2.5 μm, further preferably 0.3 to 2.0 μm, particularly preferably 0.3 to 1.7 μm, and may be 0.3 to 1.2 μm or 1.2 to 2.0 μm. If the volume average particle size of the component (X) is greater than or equal to the above lower limit, there is a tendency for excellent low thermal expansion, and if it is less than or equal to the above upper limit, there is a tendency for excellent through-hole resolution. In addition, if the volume average particle size of the component (X) is less than or equal to 2.5 μm, there is a tendency for the through-hole resolution to become very good.
[0069] From the viewpoint of improving the adhesion to the copper plating layer and the resolution of the through-hole, the component (X) may contain two or more inorganic fillers having different volume average particle sizes.
[0070] Here, the volume average particle size can be determined as follows: using a submicron particle analyzer (manufactured by Beckman Coulter, Inc., trade name: N5) in accordance with ISO13321, particles dispersed in a solvent are measured at a refractive index of 1.38, and the volume average particle size can be determined as a particle size corresponding to a cumulative value of 50% (volume basis) in the particle size distribution.
[0071] In the photosensitive resin composition of the present embodiment, the content of the component (X) is not particularly limited, and is preferably 1 to 45% by volume, more preferably 3 to 40% by volume, further preferably 5 to 40% by volume, and may be 5 to 25% by volume, or 25 to 40% by volume, based on the total solid content of the photosensitive resin composition. When the content of the component (X) is greater than or equal to the above lower limit, there is a tendency to obtain a lower relative dielectric constant and thermal expansion coefficient, and when it is less than or equal to the above upper limit, there is a tendency to obtain a better bonding strength with the copper plating layer and a better resolution of the through hole.
[0072] The photosensitive resin composition of the present embodiment preferably further contains (A) a photopolymerizable compound having an ethylenically unsaturated group and an acidic substituent and (B) a thermosetting resin. Components (A) and (B) are described in detail below in this order, and then other components are also described in detail.
[0073] <(A) Photopolymerizable Compound Having an Ethylenically Unsaturated Group and an Acidic Substituent>
[0074] (A) Component is a photopolymerizable compound having an ethylenically unsaturated group and an acidic substituent.
[0075] (A) The component may be used alone or in combination of two or more.
[0076] (A) The component is a compound that exhibits photopolymerization, particularly radical polymerization, due to having an ethylenically unsaturated group.
[0077] Examples of the ethylenically unsaturated group possessed by the component (A) include photopolymerizable functional groups such as vinyl, allyl, propargyl, butenyl, ethynyl, phenylethynyl, maleimide, nadicimide, and (meth)acryloyl. Among them, (meth)acryloyl is preferred from the viewpoint of reactivity and resolution of through-holes.
[0078] (A) Component has an acidic substituent from the viewpoint of enabling alkali development.
[0079] Examples of the acidic substituent possessed by the component (A) include a carboxyl group, a sulfonic acid group, and a phenolic hydroxyl group, etc. Among them, a carboxyl group is preferred from the viewpoint of the resolution of the through-hole.
[0080] The acid value of component (A) is preferably 20 to 200 mgKOH / g, more preferably 40 to 180 mgKOH / g, further preferably 70 to 150 mgKOH / g, and particularly preferably 90 to 120 mgKOH / g. If the acid value of component (A) is greater than or equal to the above lower limit, the solubility of the photosensitive resin film in a dilute alkaline solution tends to be excellent, and if it is less than or equal to the above upper limit, the relative dielectric constant tends to be excellent. The acid value of component (A) can be measured by the method described in the examples.
[0081] In addition, two or more (A) components having different acid values may be used in combination. In this case, the weighted average acid value of the acid values of the two or more (A) components is preferably within the above-mentioned arbitrary range.
[0082] The weight average molecular weight (Mw) of the component (A) is preferably 600 to 30,000, more preferably 800 to 25,000, further preferably 1,000 to 18,000, further preferably 1,000 to 8,000, particularly preferably 1,200 to 5,000, and most preferably 1,200 to 3,500. When the weight average molecular weight (Mw) of the component (A) is within the above range, there is a tendency for excellent bonding strength with the copper plating layer, heat resistance, and insulation reliability. Here, in this specification, the weight average molecular weight is a value obtained by converting to standard polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran as a solvent, and more specifically, a value measured by the method described in the Examples.
[0083] From the viewpoint of relative dielectric constant, the component (A) preferably contains an alicyclic skeleton.
[0084] The alicyclic skeleton possessed by the component (A) is preferably an alicyclic skeleton having 5 to 20 ring carbon atoms, more preferably an alicyclic skeleton having 5 to 18 ring carbon atoms, further preferably an alicyclic skeleton having 6 to 18 ring carbon atoms, particularly preferably an alicyclic skeleton having 8 to 14 ring carbon atoms, and most preferably an alicyclic skeleton having 8 to 12 ring carbon atoms, from the viewpoints of through-hole resolution, adhesion strength to the copper plating layer, and electrical insulation reliability.
[0085] In addition, from the viewpoints of through-hole resolution, bonding strength with copper plating, and electrical insulation reliability, the alicyclic skeleton preferably contains 2 or more rings, more preferably 2 to 4 rings, and even more preferably 3 rings. Examples of the alicyclic skeleton having 2 or more rings include a norbornane skeleton, a decalin skeleton, a bicycloundecane skeleton, and a saturated dicyclopentadiene skeleton. Among them, from the viewpoints of through-hole resolution, bonding strength with copper plating, and electrical insulation reliability, a saturated dicyclopentadiene skeleton is preferred.
[0086] From the same viewpoint, the component (A) preferably includes an alicyclic skeleton represented by the following general formula (A-1).
[0087] [Chemistry 2]
[0088]
[0089] (Where R A1 represents an alkyl group having 1 to 12 carbon atoms, which may be substituted at any position of the above-mentioned alicyclic skeleton. 1 is an integer from 0 to 6. * is a bonding site with other structures. )
[0090] In the above general formula (A-1), R A1 The alkyl group having 1 to 12 carbon atoms represented by , includes methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, etc. As the alkyl group, an alkyl group having 1 to 6 carbon atoms is preferred, an alkyl group having 1 to 3 carbon atoms is more preferred, and a methyl group is further preferred.
[0091] m 1 It is an integer of 0 to 6, preferably an integer of 0 to 2, and more preferably 0.
[0092] m 1 When it is an integer from 2 to 6, multiple R A1 They may be the same or different. A1 Substitution may be on the same carbon atom or on different carbon atoms as far as possible.
[0093] * is a bonding site with other structures, and may be bonded to any carbon atom on the alicyclic skeleton, and preferably is bonded to a carbon atom at the site represented by 1 or 2, and a carbon atom at the site represented by 3 or 4 in the following general formula (A-1').
[0094] [Chemistry 3]
[0095]
[0096] (Where R A1 、m 1 and * are the same as in the general formula (A-1). )
[0097] From the viewpoint of the resolution of the through hole and the bonding strength with the copper plating layer, the component (A) is preferably an acid-modified vinyl-containing epoxy resin, which is obtained by reacting a compound (a1) obtained by modifying an epoxy resin with an organic acid (a2) containing an ethylenically unsaturated group [hereinafter, sometimes referred to as the component (A')]. ] with a polyacid anhydride (a3) containing a saturated group or an unsaturated group. Here, the "acid-modified" of the acid-modified vinyl-containing epoxy resin means having an acidic substituent, "vinyl" means an ethylenically unsaturated group, and "epoxy resin" means using an epoxy resin as a raw material. The acid-modified vinyl-containing epoxy resin does not necessarily need to have an epoxy group and may not have an epoxy group.
[0098] Hereinafter, preferred embodiments of the component (A) obtained from (a1) an epoxy resin, (a2) an organic acid containing an ethylenically unsaturated group, and (a3) a polybasic acid anhydride containing a saturated group or an unsaturated group will be described.
[0099] ((a1) Epoxy resin)
[0100] As the (a1) epoxy resin, an epoxy resin having two or more epoxy groups is preferred.
[0101] (a1) The epoxy resin may be used alone or in combination of two or more.
[0102] (a1) Epoxy resins are classified into glycidyl ether type epoxy resins, glycidyl amine type epoxy resins, glycidyl ester type epoxy resins, etc. Among them, glycidyl ether type epoxy resins are preferred.
[0103] (a1) Epoxy resins can also be classified into various epoxy resins according to the difference in the main skeleton, and can be classified into epoxy resins having an alicyclic skeleton, novolac epoxy resins, bisphenol epoxy resins, aralkyl epoxy resins, other epoxy resins, etc. Among them, epoxy resins having an alicyclic skeleton and novolac epoxy resins are preferred.
[0104] -Epoxy resin having an alicyclic skeleton-
[0105] The alicyclic skeleton of the epoxy resin having an alicyclic skeleton is described in the same manner as the alicyclic skeleton of the above-mentioned component (A), and the preferred aspects are also the same.
[0106] As the epoxy resin having an alicyclic skeleton, an epoxy resin represented by the following general formula (A-2) is preferred.
[0107] [Chemistry 4]
[0108]
[0109] (Where R A1 represents an alkyl group having 1 to 12 carbon atoms, which may be substituted at any position of the above-mentioned alicyclic skeleton. A2 represents an alkyl group having 1 to 12 carbon atoms. 1 is an integer from 0 to 6, m 2 is an integer from 0 to 3. n is a number from 0 to 50. )
[0110] In the general formula (A-2), R A1 and R in the general formula (A-1) A1 The same, the preferred method is also the same.
[0111] As R in the general formula (A-2) A2 Examples of the alkyl group having 1 to 12 carbon atoms include methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, etc. The alkyl group is preferably an alkyl group having 1 to 6 carbon atoms, more preferably an alkyl group having 1 to 3 carbon atoms, and still more preferably a methyl group.
[0112] m in the general formula (A-2) 1 and m in the general formula (A-1) 1 The same, the preferred method is also the same.
[0113] m in the general formula (A-2) 2 It is an integer of 0 to 3, preferably 0 or 1, and more preferably 0.
[0114] n in the general formula (A-2) represents the number of repetitions of the structural unit in parentheses, and is a number from 0 to 50. Usually, the epoxy resin is a mixture of substances having different numbers of repetitions of the structural unit in parentheses, so in this case, n is represented by the average value of the mixture. As n, a number of 0 to 30 is preferred.
[0115] As the epoxy resin having an alicyclic skeleton, a commercially available item may be used, and examples of the commercially available item include XD-1000 (trade name, manufactured by Nippon Kayaku Co., Ltd.) and EPICLON (registered trademark) HP-7200 (trade name, manufactured by DIC Corporation).
[0116] -Novolac type epoxy resin-
[0117] Examples of the novolac epoxy resin include bisphenol novolac epoxy resins such as bisphenol A novolac epoxy resin, bisphenol F novolac epoxy resin, and bisphenol S novolac epoxy resin; phenol novolac epoxy resin, cresol novolac epoxy resin, biphenyl novolac epoxy resin, and naphthol novolac epoxy resin.
[0118] As the novolac-type epoxy resin, an epoxy resin having a structural unit represented by the following general formula (A-3) is preferred.
[0119] [Chemistry 5]
[0120]
[0121] (Where R A3 represents a hydrogen atom or a methyl group, Y A1 Each independently represents a hydrogen atom or a glycidyl group. A3 They can be the same or different. A1 At least one of them represents a glycidyl group. )
[0122] From the perspective of through-hole resolution and bonding strength with copper plating, R A3 Preferably, all of them are hydrogen atoms. A1 Preferably, both are glycidyl groups.
[0123] The number of structural units of the structural unit in the (a1) epoxy resin having the structural unit represented by the general formula (A-3) is 1 or more, preferably 10 to 100, more preferably 15 to 80, and further preferably 15 to 70. When the number of structural units is within the above range, there is a tendency for the bonding strength with the copper plating layer, the heat resistance, and the insulation reliability to be improved.
[0124] In the general formula (A-3), R A3 are hydrogen atoms, Y A1 The materials containing all glycidyl groups are commercially available as EXA-7376 series (manufactured by DIC Corporation, trade name). A3 All are methyl, Y A1 Those having all glycidyl groups are commercially available as EPON SU8 series (trade name, manufactured by Mitsubishi Chemical Corporation).
[0125] Examples of the bisphenol epoxy resin include bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, and 3,3′,5,5′-tetramethyl-4,4′-diglycidyloxydiphenylmethane.
[0126] Examples of the aralkyl epoxy resin include phenol aralkyl epoxy resin, biphenyl aralkyl epoxy resin, and naphthol aralkyl epoxy resin.
[0127] Other epoxy resins include stilbene-type epoxy resins, naphthalene-skeletal-containing epoxy resins, biphenyl-type epoxy resins, dihydroanthracene-type epoxy resins, cyclohexanedimethanol-type epoxy resins, trimethylol-type epoxy resins, alicyclic epoxy resins, aliphatic chain epoxy resins, heterocyclic epoxy resins, spiro-ring-containing epoxy resins, and rubber-modified epoxy resins.
[0128] ((a2) Organic acid containing ethylenically unsaturated group)
[0129] As the (a2) ethylenically unsaturated group-containing organic acid, an ethylenically unsaturated group-containing monocarboxylic acid is preferred.
[0130] As the ethylenically unsaturated group which the component (a2) has, there may be mentioned the same groups as those exemplified as the ethylenically unsaturated group which the component (A) has.
[0131] Component (a2) includes acrylic acid derivatives such as acrylic acid, acrylic acid dimer, methacrylic acid, β-furfuryl acrylate, β-styryl acrylate, cinnamic acid, crotonic acid, and α-cyanocinnamic acid; half-ester compounds of reaction products of hydroxyl-containing acrylic acid esters and dibasic acid anhydrides; and half-ester compounds of reaction products of vinyl-containing monoglycidyl ethers or vinyl-containing monoglycidyl esters and dibasic acid anhydrides.
[0132] The component (a2) may be used alone or in combination of two or more.
[0133] The half ester compound is obtained by reacting one or more ethylenically unsaturated group-containing compounds selected from the group consisting of hydroxyl-containing acrylates, vinyl-containing monoglycidyl ethers, and vinyl-containing monoglycidyl esters with a dibasic acid anhydride. The reaction is preferably carried out by reacting the ethylenically unsaturated group-containing compound and the dibasic acid anhydride in equimolar amounts.
[0134] Examples of the hydroxyl-containing acrylate used in the synthesis of the half ester compound include hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, trimethylolpropane di(meth)acrylate, pentaerythritol tri(meth)acrylate, and dipentaerythritol penta(meth)acrylate.
[0135] Examples of the vinyl group-containing monoglycidyl ether include glycidyl (meth)acrylate and the like.
[0136] The dibasic acid anhydride used in the synthesis of the above-mentioned half ester compound may contain a saturated group or an unsaturated group. Examples of the dibasic acid anhydride include succinic anhydride, maleic anhydride, tetrahydrophthalic anhydride, phthalic anhydride, methyltetrahydrophthalic anhydride, ethyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, ethylhexahydrophthalic anhydride, and itaconic anhydride.
[0137] In the reaction of component (a1) and component (a2), the amount of component (a2) used is preferably 0.6 to 1.05 equivalents, more preferably 0.7 to 1.02 equivalents, and even more preferably 0.8 to 1.0 equivalents relative to 1 equivalent of the epoxy group of component (a1). By reacting component (a1) and component (a2) at the above ratio, there is a tendency that the photopolymerizability of component (A) is improved and the resolution of the through-holes of the obtained photosensitive resin composition is improved.
[0138] The components (a1) and (a2) are preferably dissolved in an organic solvent for reaction.
[0139] Examples of the organic solvent include ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ether compounds such as methyl cellosolve, butyl cellosolve, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol diethyl ether, and triethylene glycol monoethyl ether; esters such as ethyl acetate, butyl acetate, butyl cellosolve acetate, and carbitol acetate; aliphatic hydrocarbons such as octane and decane; petroleum solvents such as petroleum ether, naphtha, hydrogenated naphtha, and solvent naphtha, etc. The organic solvent may be used alone or in combination of two or more.
[0140] In the reaction of component (a1) and component (a2), a catalyst for promoting the reaction is preferably used. Examples of the catalyst include amine catalysts such as triethylamine and benzylmethylamine; quaternary ammonium salt catalysts such as methyltriethylammonium chloride, benzyltrimethylammonium chloride, benzyltrimethylammonium bromide, and benzyltrimethylammonium iodide; and phosphine catalysts such as triphenylphosphine. Among them, phosphine catalysts are preferred, and triphenylphosphine is more preferred. The catalyst may be used alone or in combination of two or more.
[0141] When a catalyst is used, the amount used is preferably 0.01 to 10 parts by mass, more preferably 0.05 to 5 parts by mass, and even more preferably 0.1 to 2 parts by mass based on 100 parts by mass of the total of the components (a1) and (a2), from the viewpoint of obtaining an appropriate reaction rate.
[0142] In the reaction of component (a1) and component (a2), a polymerization inhibitor is preferably used for the purpose of preventing polymerization during the reaction. Examples of the polymerization inhibitor include hydroquinone, methylhydroquinone, hydroquinone monomethyl ether, catechol, pyrogallol, etc. The polymerization inhibitor may be used alone or in combination of two or more.
[0143] When a polymerization inhibitor is used, the amount used is preferably 0.01 to 1 part by mass, more preferably 0.02 to 0.8 part by mass, and even more preferably 0.1 to 0.5 part by mass, based on 100 parts by mass of the total of the components (a1) and (a2).
[0144] The reaction temperature of the components (a1) and (a2) is preferably 60 to 150°C, more preferably 80 to 120°C, and even more preferably 90 to 110°C from the viewpoint of obtaining sufficient reactivity and homogeneously reacting.
[0145] As described above, when a monocarboxylic acid containing an ethylenically unsaturated group is used as the component (a2), the component (A') obtained by reacting the components (a1) and (a2) has a hydroxyl group formed by a ring-opening addition reaction between the epoxy group of the component (a1) and the carboxyl group of the component (a2). Then, by reacting the component (A') with the component (a3), an acid-modified vinyl-containing epoxy resin can be obtained in which the hydroxyl group of the component (A') (including the hydroxyl group originally present in the component (a1)) and the acid anhydride group of the component (a3) are half-esterified.
[0146] ((a3) polyacid anhydride)
[0147] As (a3) component, it is possible to contain a saturated group or an unsaturated group. As (a3) component, succinic anhydride, maleic anhydride, tetrahydrophthalic anhydride, phthalic anhydride, methyltetrahydrophthalic anhydride, ethyltetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, ethylhexahydrophthalic anhydride, itaconic anhydride etc. can be listed. Among them, from the viewpoint of the resolution of through hole, tetrahydrophthalic anhydride is preferred. (a3) component can be used alone or in combination of two or more.
[0148] In the reaction between the components (A') and (a3), for example, 0.1 to 1.0 equivalent of the component (a3) is reacted per 1 equivalent of the hydroxyl group in the component (A'), whereby the acid value of the acid-modified vinyl-containing epoxy resin can be adjusted.
[0149] The reaction temperature of the component (A') and the component (a3) is preferably 50 to 150°C, more preferably 60 to 120°C, and even more preferably 70 to 100°C from the viewpoint of obtaining sufficient reactivity and homogeneously reacting.
[0150] The content of the component (A) in the photosensitive resin composition of the present embodiment is not particularly limited, but is preferably 10 to 80% by mass, more preferably 10 to 60% by mass, further preferably 15 to 45% by mass, particularly preferably 15 to 35% by mass, and most preferably 20 to 35% by mass, based on the total amount of the resin components in the photosensitive resin composition, from the viewpoints of heat resistance, relative dielectric constant, and chemical resistance.
[0151] <(B) Thermosetting resin>
[0152] The component (B) is a thermosetting resin and does not contain the component (A).
[0153] The photosensitive resin composition of the present embodiment tends to have improved heat resistance in addition to improved bonding strength with the copper plating layer and improved insulation reliability by containing the (B) thermosetting resin.
[0154] Examples of thermosetting resins include epoxy resins, phenolic resins, unsaturated imide resins, cyanate resins, isocyanate resins, benzoxazine resins, oxetane resins, amino resins, unsaturated polyester resins, allyl resins, dicyclopentadiene resins, silicone resins, triazine resins, and melamine resins. In addition, the above resins are not particularly limited, and known thermosetting resins can be used. Among them, epoxy resins are preferred from the viewpoints of bonding strength to the copper plating layer, insulation reliability, and heat resistance.
[0155] (B) The component may be used alone or in combination of two or more.
[0156] As the epoxy resin, an epoxy resin having two or more epoxy groups is preferred. Epoxy resins are classified into glycidyl ether type epoxy resins, glycidyl amine type epoxy resins, glycidyl ester type epoxy resins, etc. Among them, glycidyl ether type epoxy resins are preferred.
[0157] In addition, epoxy resins are also classified into various epoxy resins according to the difference of the main skeleton. Among the above-mentioned various types of epoxy resins, they can be further classified as follows. Specifically, they can be classified into bisphenol-based epoxy resins such as bisphenol A epoxy resin, bisphenol F epoxy resin, and bisphenol S epoxy resin; bisphenol-based novolac epoxy resins such as bisphenol A novolac epoxy resin and bisphenol F novolac epoxy resin; novolac epoxy resins other than the above-mentioned bisphenol-based novolac epoxy resins such as phenol novolac epoxy resin, cresol novolac epoxy resin, and biphenyl novolac epoxy resin; phenol aralkyl epoxy resin; stilbene epoxy resin; naphthol phenol Epoxy resins containing naphthalene skeletons such as aldehyde varnish type epoxy resins, naphthol type epoxy resins, naphthol aralkyl type epoxy resins, and naphthylene ether type epoxy resins; biphenyl type epoxy resins; biphenyl aralkyl type epoxy resins; diphenyl dimethyl type epoxy resins; dihydroanthracene type epoxy resins; alicyclic epoxy resins such as saturated dicyclopentadiene type epoxy resins; heterocyclic epoxy resins; epoxy resins containing spiro rings; cyclohexanedimethanol type epoxy resins; trimethylol type epoxy resins; aliphatic chain epoxy resins; rubber modified epoxy resins, etc.
[0158] Among them, in particular, from the viewpoints of heat resistance, electrical insulation reliability, developability and bonding strength with the copper plating layer, the epoxy resin preferably contains at least one selected from the group consisting of bisphenol epoxy resins, naphthalene skeleton-containing epoxy resins and biphenyl aralkyl type epoxy resins, and more preferably contains at least one selected from the group consisting of naphthalene skeleton-containing epoxy resins and biphenyl aralkyl type epoxy resins.
[0159] The equivalent ratio [epoxy group / acidic substituent] of the acidic substituent of the component (A) and the epoxy group of the component (B) in the photosensitive resin composition of the present embodiment is not particularly limited, but is preferably 0.5 to 6.0, more preferably 0.7 to 4.0, further preferably 0.8 to 2.0, and particularly preferably 0.9 to 1.8 from the viewpoint of insulation reliability, relative dielectric constant, heat resistance, and adhesion strength to the copper plating layer.
[0160] The content of the component (B) in the photosensitive resin composition of the present embodiment is not particularly limited, but is preferably 1 to 50% by mass, more preferably 5 to 30% by mass, and even more preferably 10 to 25% by mass based on the total amount of the resin components in the photosensitive resin composition from the viewpoints of insulation reliability, relative dielectric constant, heat resistance, and adhesion strength to the copper plating layer.
[0161] <(C) Cross-linking agent>
[0162] The photosensitive resin composition of the present embodiment preferably further contains a crosslinking agent as component (C). As a crosslinking agent, a crosslinking agent having two or more ethylenically unsaturated groups and having no acidic substituent is preferred. The crosslinking agent reacts with the ethylenically unsaturated groups possessed by component (A) to increase the crosslinking density of the photosensitive resin film after curing. Therefore, the photosensitive resin composition of the present embodiment has a tendency to further improve heat resistance and relative dielectric constant by containing a crosslinking agent.
[0163] (C) The component may be used alone or in combination of two or more.
[0164] As the component (C), there can be mentioned a bifunctional monomer having two ethylenically unsaturated groups and a polyfunctional monomer having three or more ethylenically unsaturated groups. The component (C) preferably contains the above-mentioned polyfunctional monomer.
[0165] As the ethylenically unsaturated group which the component (C) has, there can be mentioned the same groups as the ethylenically unsaturated group which the component (A) has, and preferred groups are also the same.
[0166] Examples of the difunctional monomer include aliphatic di(meth)acrylates such as trimethylolpropane di(meth)acrylate, polypropylene glycol di(meth)acrylate, and polyethylene glycol di(meth)acrylate; di(meth)acrylates having an alicyclic skeleton such as dicyclopentadiene di(meth)acrylate and tricyclodecane dimethanol di(meth)acrylate; and aromatic di(meth)acrylates such as 2,2-bis(4-(meth)acryloyloxypolyethoxypolypropoxyphenyl)propane and bisphenol A diglycidyl ether di(meth)acrylate.
[0167] Among them, from the viewpoint of obtaining a lower relative dielectric constant, di(meth)acrylates having an alicyclic skeleton are preferred, and tricyclodecane dimethanol diacrylate is more preferred.
[0168] Examples of the polyfunctional monomer include (meth)acrylate compounds having a skeleton derived from trimethylolpropane such as trimethylolpropane tri(meth)acrylate; (meth)acrylate compounds having a skeleton derived from tetramethylolmethane such as tetramethylolmethane tri(meth)acrylate and tetramethylolmethane tetra(meth)acrylate; (meth)acrylate compounds having a skeleton derived from pentaerythritol such as pentaerythritol tri(meth)acrylate and pentaerythritol tetra(meth)acrylate; (meth)acrylate compounds having a skeleton derived from dipentaerythritol such as dipentaerythritol penta(meth)acrylate and dipentaerythritol hexa(meth)acrylate; (meth)acrylate compounds having a skeleton derived from di(trimethylolpropane) such as di(trimethylolpropane) tetra(meth)acrylate; (meth)acrylate compounds having a skeleton derived from diglycerol, and the like. Among them, from the viewpoint of the resolution of the through-hole and the bonding strength with the copper plating layer, a (meth)acrylate compound having a skeleton derived from trimethylolpropane is preferred, and trimethylolpropane tri(meth)acrylate is more preferred.
[0169] Here, the above-mentioned “(meth)acrylate compound having a skeleton derived from XXX” (wherein XXX is a compound name) refers to an esterification product of XXX and (meth)acrylic acid, and the esterification product also includes compounds modified with an alkenyloxy group.
[0170] When the photosensitive resin composition of the present embodiment contains the crosslinking agent (C), the content of the crosslinking agent (C) is not particularly limited, but is preferably 10 to 85 parts by mass, more preferably 25 to 80 parts by mass, further preferably 35 to 75 parts by mass, and particularly preferably 35 to 60 parts by mass, relative to 100 parts by mass of the component (A), from the viewpoint of heat resistance and relative dielectric constant.
[0171] <(D) Elastomer>
[0172] The photosensitive resin composition of the present embodiment preferably further contains an elastomer as the component (D). The photosensitive resin composition of the present embodiment has a tendency to further improve the bonding strength with the copper plating layer by containing the elastomer (D). In addition, the photosensitive resin composition of the present embodiment has a tendency to suppress the effect of "reduction in flexibility and bonding strength with the copper plating layer" caused by the strain (internal stress) that may be generated due to the curing shrinkage of the above-mentioned component (A) by containing the elastomer (D).
[0173] (D) The elastomer may be used alone or in combination of two or more.
[0174] (D) The elastomer may have a reactive functional group at a molecular terminal or in a molecular chain.
[0175] Examples of the reactive functional group include an acid anhydride group, an epoxy group, a hydroxyl group, a carboxyl group, an amino group, an amide group, an isocyanate group, an acryloyl group, a methacryloyl group, and a vinyl group. Among them, from the viewpoint of the resolution of the through hole and the bonding strength with the copper plating layer, an acid anhydride group, an epoxy group, a hydroxyl group, a carboxyl group, an amino group, and an amide group are preferred, an acid anhydride group and an epoxy group are more preferred, and an acid anhydride group is further preferred.
[0176] The acid anhydride group is preferably an acid anhydride group derived from phthalic anhydride, maleic anhydride, trimellitic anhydride, pyromellitic anhydride, hexahydrophthalic anhydride, tetrahydrophthalic anhydride, methyl nadic anhydride, nadic anhydride, glutaric anhydride, dimethyl glutaric anhydride, diethyl glutaric anhydride, succinic anhydride, methyl hexahydrophthalic anhydride, methyl tetrahydrophthalic anhydride or the like, and more preferably an acid anhydride group derived from maleic anhydride.
[0177] (D) When the elastomer has an acid anhydride group, the number of the acid anhydride groups in one molecule is preferably 1 to 10, more preferably 3 to 10, and even more preferably 6 to 10, from the viewpoint of through-hole resolution and relative dielectric constant.
[0178] The photosensitive resin composition of the present embodiment preferably contains an elastomer having an ethylenically unsaturated group and an acidic substituent as the (D) elastomer.
[0179] The acidic substituent and ethylenically unsaturated group may be the same as those contained in the component (A). The elastomer (D) preferably has the above-mentioned acid anhydride group as the acidic substituent and the 1,2-vinyl group described below as the ethylenically unsaturated group.
[0180] (D) Elastomers include polybutadiene elastomers, polyester elastomers, styrene elastomers, olefin elastomers, urethane elastomers, polyamide elastomers, acrylic elastomers, silicone elastomers, and derivatives of these elastomers. Among them, polybutadiene elastomers are preferred from the viewpoints of improving the bonding strength with the copper plating layer and improving the compatibility and solubility with the resin component.
[0181] Preferred examples of the polybutadiene elastomer include a polybutadiene elastomer containing a 1,2-vinyl group and having a structural unit of a 1,4-trans isomer and a structural unit of a 1,4-cis isomer.
[0182] As described above, from the viewpoint of the resolution of the through-holes, the polybutadiene elastomer is preferably a polybutadiene elastomer having an acid anhydride group modified with an acid anhydride, and more preferably a polybutadiene elastomer having an acid anhydride group derived from maleic anhydride.
[0183] Polybutadiene-based elastomers are commercially available, and specific examples thereof include "POLYVEST (registered trademark) MA75", "POLYVEST (registered trademark) EP MA120" (each manufactured by Evonik and a trade name), "Ricon (registered trademark) 100", "Ricon (registered trademark) 130MA8", "Ricon (registered trademark) 131MA5", "Ricon (registered trademark) 131MA17", and "Ricon (registered trademark) 184MA6" (each manufactured by Cray Valley and a trade name).
[0184] From the viewpoint of the bonding strength with the copper plating layer, the polybutadiene-based elastomer may be polybutadiene having an epoxy group [hereinafter, sometimes referred to as epoxidized polybutadiene].
[0185] From the viewpoint of the bonding strength with the copper plating layer and the flexibility, the epoxidized polybutadiene is preferably an epoxidized polybutadiene represented by the following general formula (D-1).
[0186] [Chemistry 6]
[0187]
[0188] (In the formula, a, b and c represent the ratio of the structural units in the parentheses, respectively, a is 0.05 to 0.40, b is 0.02 to 0.30, c is 0.30 to 0.80, and further, a+b+c=1.00, and (a+c)> satisfies b. y represents the number of structural units in the square brackets, which is an integer of 10 to 250.)
[0189] In the above general formula (D-1), the bonding order of each structural unit in the square brackets is different. That is, the structural units shown on the left, the structural units shown in the center, and the structural units shown on the right can be interchanged. If they are represented by (a), (b), and (c), respectively, there can be various combination orders such as -[(a)-(b)-(c)]-[(a)-(b)-(c)-]-, -[(a)-(c)-(b)]-[(a)-(c)-(b)-]-, -[(b)-(a)-(c)]-[(b)-(a)-(c)-]-, -[(a)-(b)-(c)]-[(c)-(b)-(a)-]-, -[(a)-(b)-(c)]-[(c)-(b)-(a)-]-, -[(a)-(b)-(a)]-[(c)-(b)-(c)-]-, -[(c)-(b)-(c)]-[(b)-(a)-(a)-]-
[0190] From the viewpoint of the bonding strength with the copper plating layer and the flexibility, a is preferably 0.10 to 0.30, b is preferably 0.10 to 0.30, and c is preferably 0.40 to 0.80. From the same viewpoint, y is preferably an integer of 30 to 180.
[0191] Examples of the polyester elastomer include polyester elastomers obtained by polycondensation of a dicarboxylic acid or a derivative thereof and a diol compound or a derivative thereof.
[0192] Examples of the dicarboxylic acid include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, and naphthalene dicarboxylic acid, and aromatic dicarboxylic acids in which hydrogen atoms of the aromatic nuclei are substituted with methyl, ethyl, phenyl, and the like; aliphatic dicarboxylic acids having 2 to 20 carbon atoms such as adipic acid, sebacic acid, and dodecanedicarboxylic acid; and alicyclic dicarboxylic acids such as cyclohexanedicarboxylic acid.
[0193] Examples of the diol compound include aliphatic diols such as ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, and 1,10-decanediol; alicyclic diols such as 1,4-cyclohexanediol; and aromatic diols such as bisphenol A, bis(4-hydroxyphenyl)methane, bis(4-hydroxy-3-methylphenyl)propane, and resorcinol.
[0194] In addition, as the polyester elastomer, preferably, there can be mentioned a multi-block copolymer having an aromatic polyester (e.g., polybutylene terephthalate) portion as a hard segment component and an aliphatic polyester (e.g., polytetramethylene glycol) portion as a soft segment component. The multi-block copolymer has various grades depending on the type, ratio, and molecular weight of the hard segment and the soft segment.
[0195] The number average molecular weight of the (D) elastomer is not particularly limited, but is preferably 10,000 to 80,000, 20,000 to 70,000, 30,000 to 65,000, or 40,000 to 60,000. The number average molecular weight of the (D) elastomer is determined by standard polystyrene conversion using gel permeation chromatography (GPC) using tetrahydrofuran as a solvent.
[0196] When the photosensitive resin composition of the present embodiment contains the elastomer (D), the content of the elastomer (D) is not particularly limited, but is preferably 0.5 to 15% by mass, more preferably 1 to 10% by mass, further preferably 1 to 8% by mass, and particularly preferably 3 to 8% by mass, based on the total amount of the resin components of the photosensitive resin composition, from the viewpoint of heat resistance and adhesion strength to the copper plating layer.
[0197] <(E) Organic filler>
[0198] The photosensitive resin composition of the present embodiment may further contain an organic filler as the (E) component. The photosensitive resin composition of the present embodiment contains the (E) organic filler, so that the photosensitive resin composition and the photosensitive resin film tend to have a low specific gravity, and depending on the material, there is sometimes a tendency for the relative dielectric constant to be further reduced.
[0199] The component (E) preferably comprises resin particles formed of at least one selected from the group consisting of a resin having a fluorine atom, polyethylene, polypropylene, polystyrene, polyphenylene ether and silicone. Among them, from the viewpoint of the effect of reducing the relative dielectric constant, the component (E) preferably comprises resin particles formed of a resin having a fluorine atom, and more preferably comprises resin particles formed of a polytetrafluoroethylene (PTFE) resin.
[0200] The volume average particle size of the resin particles is not particularly limited, but is preferably 20 to 1,000 nm, more preferably 30 to 800 nm, further preferably 50 to 500 nm, and particularly preferably 100 to 300 nm. The method for measuring the volume average particle size is as described above.
[0201] When the photosensitive resin composition of the present embodiment contains (E) an organic filler, the content of the (E) organic filler is not particularly limited, and is preferably 1 to 45% by mass, more preferably 3 to 40% by mass, further preferably 5 to 30% by mass, and particularly preferably 10 to 30% by mass, based on the total amount of the resin components of the photosensitive resin composition. When the content of the (E) organic filler is greater than or equal to the above lower limit value based on the total amount of the resin components of the photosensitive resin composition, there is a tendency to further reduce the relative dielectric constant, and when it is less than or equal to the above upper limit value, there is a tendency to suppress the reduction in the bonding strength with the copper plating layer. From the same viewpoint, the content of the resin having fluorine atoms, in particular, is preferably 1 to 45% by mass, more preferably 3 to 40% by mass, further preferably 5 to 30% by mass, and particularly preferably 10 to 30% by mass, based on the total amount of the resin components of the photosensitive resin composition.
[0202] In particular, when the (E) organic filler contains resin particles formed of a resin having fluorine atoms, the total amount of the (X) component and the (E) component is preferably less than or equal to 50% by volume, more preferably less than or equal to 45% by volume, and further preferably less than or equal to 40% by volume based on the total amount of the resin components of the photosensitive resin composition from the viewpoint of bonding strength with the copper plating layer. The lower limit of the total amount of the (X) component and the (E) component is not particularly limited, but from the viewpoint of reducing the relative dielectric constant, it is preferably greater than or equal to 2% by volume, more preferably greater than or equal to 10% by volume, further preferably greater than or equal to 20% by volume, and particularly preferably greater than or equal to 30% by volume.
[0203] <(F) Curing agent>
[0204] The photosensitive resin composition of the present embodiment preferably further contains a curing agent as the component (F). The photosensitive resin composition of the present embodiment tends to be able to further improve heat resistance, relative dielectric constant, and the like by containing the curing agent (F).
[0205] (F) The curing agent may be used alone or in combination of two or more.
[0206] As (F) curing agent, the curing agent for the above-mentioned (B) thermosetting resin can be used. For example, when the above-mentioned (B) thermosetting resin is an epoxy resin, it is preferred to use an epoxy resin curing agent. Examples of the epoxy resin curing agent include guanamines such as acetoguanamine and benzoguanamine; polyamines such as diaminodiphenylmethane, metaphenylenediamine, metaxylene diamine, diaminodiphenyl sulfone, dicyandiamide, urea, urea derivatives, melamine, and polyhydrazides; their organic acid salts and / or epoxy adducts; amine complexes of boron trifluoride; triazine derivatives such as ethyldiamino-s-triazine, 2,4-diamino-s-triazine, and 2,4-diamino-6-xylyl-s-triazine; polyphenols such as polyvinylphenol, polyvinylphenol bromide, phenol novolac, alkylphenol novolac, and phenol novolac resin containing a triazine ring, etc.
[0207] The polyphenols may be, for example, modified polyphenols modified with melamine, benzoguanamine, etc. The hydroxyl equivalent of the polyphenols is not particularly limited, but is preferably 40 g / eq to 300 g / eq, 40 g / eq to 250 g / eq, 60 g / eq to 200 g / eq, 80 g / eq to 160 g / eq, or 100 g / eq to 140 g / eq. Here, the hydroxyl equivalent (g / eq) may be determined by titration using an acetylation method using acetic anhydride.
[0208] When the photosensitive resin composition of the present embodiment contains (F) a curing agent, the content of the (F) curing agent is not particularly limited, but is preferably 0.01 to 10% by mass, more preferably 0.05 to 5% by mass, and even more preferably 0.1 to 1% by mass, based on the total amount of the resin components of the photosensitive resin composition, from the viewpoint of further improving heat resistance and relative dielectric constant.
[0209] <(G) Curing Accelerator>
[0210] The photosensitive resin composition of the present embodiment preferably further contains a curing accelerator as the component (G). The photosensitive resin composition of the present embodiment tends to be able to further improve heat resistance, relative dielectric constant, and the like by containing the curing accelerator (G).
[0211] (G) The curing accelerator may be used alone or in combination of two or more.
[0212] (G) The curing accelerator includes imidazole compounds such as 2-methylimidazole, 2-ethyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 2-phenylimidazole, 2-phenyl-1-benzyl-1H-imidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, and isocyanate-blocked imidazole (addition reaction product of hexamethylene diisocyanate resin and 2-ethyl-4-methylimidazole); tertiary amines such as trimethylamine, N,N-dimethyloctylamine, N-benzyldimethylamine, pyridine, N-methylmorpholine, hexa(N-methyl)melamine, 2,4,6-tris(dimethylaminophenol), tetramethylguanidine, and m-aminophenol; organic phosphines such as tributylphosphine, triphenylphosphine, and tri-2-cyanoethylphosphine; tri-n-butyl(2,5-dihydroxyphenyl)bromide; Hexadecyl tributyl chloride wait Salts; quaternary ammonium salts such as benzyltrimethylammonium chloride and phenyltributylammonium chloride; the above-mentioned polyacid anhydrides; diphenyl iodide Tetrafluoroborate, triphenylsulfonium hexafluoroantimonate, 2,4,6-triphenylthiopyran Hexafluorophosphate, etc.
[0213] Among them, imidazole compounds are preferred from the viewpoint of obtaining an excellent curing effect.
[0214] When the photosensitive resin composition of the present embodiment contains (G) a curing accelerator, the content of the (G) curing accelerator is not particularly limited, but is preferably 0.01 to 10% by mass, more preferably 0.05 to 5% by mass, and even more preferably 0.1 to 2% by mass, based on the total amount of the resin components of the photosensitive resin composition, from the viewpoint of further improving heat resistance and relative dielectric constant.
[0215] <(H) Photopolymerization Initiator>
[0216] The photosensitive resin composition of the present embodiment preferably further contains a photopolymerization initiator as the component (H). The photosensitive resin composition of the present embodiment tends to further improve the resolution of the through-hole by containing the (H) photopolymerization initiator.
[0217] (H) The photopolymerization initiator may be used alone or in combination of two or more. From the viewpoint of the resolution of the through-hole, the photosensitive resin composition of the present embodiment preferably contains two or more (H) components.
[0218] (H) The photopolymerization initiator is not particularly limited as long as it can photopolymerize an ethylenically unsaturated group, and can be appropriately selected from commonly used photopolymerization initiators.
[0219] (H) The photopolymerization initiator includes benzoin compounds such as benzoin, benzoin methyl ether, and benzoin isopropyl ether; acetophenone compounds such as acetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 1,1-dichloroacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-1-butanone, 2-[4-(methylthio)benzoyl]-2-(4-morpholino)propane, and N,N-dimethylaminoacetophenone; 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 1-chloroanthraquinone, 2-amylanthraquinone, Anthraquinone compounds such as 2-aminoanthraquinone; ketal compounds such as acetophenone dimethyl ketal and benzil dimethyl ketal; acridine compounds such as 9-phenylacridine and 1,7-bis(9,9'-acridinyl)heptane; acylphosphine oxide compounds such as bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide; oxime ester compounds such as 1,2-octanedione-[4-(phenylthio)phenyl]-2-(O-benzoyl oxime), 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetyl oxime), and 1-phenyl-1,2-propanedione-2-[O-(ethoxycarbonyl)oxime], etc.
[0220] Among them, oxime ester compounds and acylphosphine oxide compounds are preferred, and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone 1-(O-acetoxime) and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide are more preferred. Oxime ester compounds have the advantage of improving photocurability, and acylphosphine oxide compounds have the advantages of improving the curing degree of the bottom of the cured product obtained by curing the photosensitive resin film and inhibiting undercutting. By using oxime ester compounds and acylphosphine oxide compounds in combination, there is a tendency for the resolution of the through-hole to be further improved.
[0221] When the photosensitive resin composition of the present embodiment contains a photopolymerization initiator (H), the content of the photopolymerization initiator (H) is not particularly limited, but is preferably 0.01 to 20% by mass, more preferably 0.05 to 10% by mass, further preferably 0.05 to 3% by mass, and particularly preferably 0.05 to 1.0% by mass, based on the total amount of the resin components of the photosensitive resin composition. When the content of the photopolymerization initiator (H) is greater than or equal to the lower limit, there is a tendency to reduce the dissolution of the exposed portion during development, and when it is less than or equal to the upper limit, there is a tendency to improve the heat resistance.
[0222] <(I) Photosensitizer>
[0223] The photosensitive resin composition of the present embodiment may contain a photosensitizer as the component (I) as necessary.
[0224] (I) The photosensitizer may be used alone or in combination of two or more. From the viewpoint of the resolution of the through-hole, the photosensitive resin composition of the present embodiment may contain two or more components (I).
[0225] Examples of the photosensitizer (I) include thioxanthone compounds such as 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 2-chlorothioxanthone, and 2,4-diisopropylthioxanthone; tertiary amines such as trialkylamines and triethanolamine; dialkylaminobenzoic acid alkyl esters such as ethyl N,N-dimethylaminobenzoate and amyl N,N-dimethylaminobenzoate; bis(dialkylamino)benzophenones such as 4,4'-bis(dimethylamino)benzophenone and 4,4'-bis(diethylamino)benzophenone; phosphine compounds such as triphenylphosphine; toluidine compounds such as N,N-dimethyltoluidine; anthracene compounds such as 9,10-dimethoxyanthracene, 2-ethyl-9,10-dimethoxyanthracene, and 2-ethyl-9,10-diethoxyanthracene; perylene compounds; coumarin compounds, and the like.
[0226] As the photosensitizer (I), from the viewpoint of improving the resolution of the through-hole and the shape of the through-hole, preferably bis(dialkylamino)benzophenone, more preferably 4,4′-bis(diethylamino)benzophenone.
[0227] When the photosensitive resin composition of the present embodiment contains (I) a photosensitizer, the content of the photosensitizer (I) is not particularly limited, but is preferably 0.01 to 5% by mass, more preferably 0.05 to 3% by mass, further preferably 0.1 to 1.5% by mass, and particularly preferably 0.1 to 1.0% by mass, based on the total amount of the resin components of the photosensitive resin composition. If the content of the photosensitizer (I) is greater than or equal to the above lower limit, the curing degree of the bottom of the cured product obtained by curing the photosensitive resin film tends to be sufficiently high, and if it is less than or equal to the above upper limit, the curing degree of the bottom of the cured product tends to be appropriately low.
[0228] <(J) Additives>
[0229] The photosensitive resin composition of the present embodiment may contain inorganic fillers other than the above-mentioned component (X) as needed; pigments such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, carbon black, naphthalene black, etc.; adhesive aids such as melamine; foam stabilizers such as silicone compounds; inhibitors; thickeners; flame retardants, etc., and various well-known and commonly used additives.
[0230] The content of these (J) additives may be appropriately adjusted depending on the purpose, and each is preferably 0.01 to 5% by mass, 0.05 to 3% by mass, or 0.1 to 1% by mass based on the total amount of the resin components of the photosensitive resin composition.
[0231] <Thinner>
[0232] The photosensitive resin composition of the present embodiment may contain a diluent as needed. As the diluent, an organic solvent or the like may be used. As the organic solvent, ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ether compounds such as methyl cellosolve, butyl cellosolve, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monoethyl ether, dipropylene glycol diethyl ether, and triethylene glycol monoethyl ether; esters such as ethyl acetate, butyl acetate, propylene glycol monoethyl ether acetate, butyl cellosolve acetate, and carbitol acetate; aliphatic hydrocarbons such as octane and decane; petroleum solvents such as petroleum ether, naphtha, hydrogenated naphtha, and solvent naphtha, etc. The diluent may be used alone or in combination of two or more.
[0233] When the photosensitive resin composition of the present embodiment contains a diluent, the content of the diluent can be appropriately selected for the purpose of adjusting the concentration of the total solid content in the photosensitive resin composition to preferably 40 to 90% by mass, more preferably 50 to 85% by mass, and further preferably 60 to 80% by mass. By adjusting the amount of the diluent used to the above range, the coating properties of the photosensitive resin composition are improved, and a higher-definition pattern can be formed.
[0234] The photosensitive resin composition of the present embodiment can be obtained by kneading and mixing the components using a roll mill, a bead mill, or the like.
[0235] Here, the photosensitive resin composition of the present embodiment may be used in a liquid state (liquid state) or in a film state (film state).
[0236] When used in a liquid state, the coating method of the photosensitive resin composition of the present embodiment is not particularly limited, and various coating methods can be cited, such as printing, spin coating, spray coating, jet dispensing, inkjet, dip coating, etc. Among them, printing and spin coating are preferred from the viewpoint of easier formation of a photosensitive layer.
[0237] In addition, when used in a film form, for example, it can be used in the form of a photosensitive resin film described later, in which case a photosensitive layer of a desired thickness can be formed by stacking it on a carrier film using a laminator, etc. It should be noted that when used in a film form, the manufacturing efficiency of a multilayer printed wiring board becomes high, so it is preferred.
[0238] The photosensitive resin composition of the present embodiment is suitable for through-hole formation by photolithography (also referred to as optical through-hole formation). Therefore, the present disclosure also provides a photosensitive resin composition for through-hole formation formed from the photosensitive resin composition of the present embodiment.
[0239] [Photosensitive resin film]
[0240] The photosensitive resin film of this embodiment is formed using the photosensitive resin composition of this embodiment. This photosensitive resin film is useful as a photosensitive layer for forming an interlayer insulating layer.
[0241] The photosensitive resin film of this embodiment may be provided on a carrier film.
[0242] The photosensitive resin film of the present embodiment can be formed by coating the photosensitive resin composition of the present embodiment on a carrier film using a known coating apparatus such as a notch wheel coater, a bar coater, a kiss coater, a roll coater, a gravure coater, or a die coater, and drying the coating.
[0243] Examples of the carrier film include polyesters such as polyethylene terephthalate and polybutylene terephthalate, and polyolefins such as polypropylene and polyethylene. The thickness of the carrier film is preferably 5 to 100 μm, more preferably 10 to 60 μm, and even more preferably 15 to 45 μm.
[0244] In addition, the photosensitive resin film of this embodiment may also be provided with a protective film on the surface opposite to the surface in contact with the carrier film. As the protective film, a polymer film such as polyethylene or polypropylene may be used. In addition, the same polymer film as the above-mentioned carrier film may be used, or a different polymer film may be used.
[0245] The drying of the coating formed by applying the photosensitive resin composition can use a dryer using hot air drying, far infrared or near infrared rays, etc. As the drying temperature, it is preferably 60 to 150°C, more preferably 70 to 120°C, and further preferably 80 to 110°C. In addition, as the drying time, it is preferably 1 minute to 60 minutes, more preferably 2 minutes to 30 minutes, and further preferably 5 minutes to 20 minutes. From the viewpoint of avoiding diluent diffusion in the manufacturing process of the multilayer printed wiring board, the content of the residual diluent in the dried photosensitive resin film is preferably less than or equal to 3% by mass, more preferably less than or equal to 2% by mass, and further preferably less than or equal to 1% by mass.
[0246] The thickness (thickness after drying) of the photosensitive resin film (photosensitive layer) is not particularly limited, but is preferably 1 to 100 μm, more preferably 3 to 50 μm, and even more preferably 5 to 40 μm from the viewpoint of reducing the thickness of the multilayer printed wiring board.
[0247] The photosensitive resin film of the present embodiment is excellent in the resolution of through holes and the bonding strength with the copper plating layer, and therefore is suitable as an interlayer insulating layer of a multilayer printed wiring board.
[0248] [Multilayer printed wiring board and method for manufacturing the same]
[0249] The multilayer printed wiring board of the present embodiment includes an interlayer insulating layer formed using the photosensitive resin composition of the present embodiment or the photosensitive resin film of the present embodiment. Here, the expression "including an interlayer insulating layer" also includes the case where the interlayer insulating layer is directly included and the case where the interlayer insulating layer is included in a state where the interlayer insulating layer is subjected to various treatments such as through-hole formation, roughening treatment, and wiring formation.
[0250] The multilayer printed wiring board of this embodiment is not particularly limited in its production method as long as it has a step of forming an interlayer insulating layer using the photosensitive resin composition or photosensitive resin film of this embodiment, and can be more easily produced by, for example, the following method for producing a multilayer printed wiring board of this embodiment.
[0251] Appropriate reference Figure 1 A method for producing a multilayer printed wiring board using the photosensitive resin film of the present embodiment will be described.
[0252] The multilayer printed wiring board 100A is manufactured, for example, by a manufacturing method including the following (1) to (4) [wherein (3) is arbitrary].
[0253] (1): The photosensitive resin film of the present embodiment is laminated on one surface or both surfaces of a circuit board (hereinafter referred to as "lamination step (1)").
[0254] (2): The photosensitive resin film laminated in step (1) is exposed and developed to form an interlayer insulating layer having a through hole (hereinafter referred to as "optical through hole forming step (2)").
[0255] (3): The through hole and the interlayer insulating layer are subjected to a roughening treatment (hereinafter referred to as "roughening treatment step (3)").
[0256] (4): A circuit pattern is formed on the interlayer insulating layer (hereinafter referred to as "circuit pattern forming step (4)").
[0257] Here, in this specification, as described above, for convenience, a predetermined operation may be referred to as "XX step" in some cases, but the XX step is not limited to the method specifically described in this specification.
[0258] (Lamination process (1))
[0259] The lamination step (1) is a step of laminating the photosensitive resin film of the present embodiment on one or both sides of a circuit substrate (substrate 101 having a circuit pattern 102) using a vacuum laminator. Examples of the vacuum laminator include a vacuum applicator manufactured by Nichigo-Morton Co., Ltd., a vacuum pressure laminator manufactured by Meiki Mfg. Co., Ltd., a roll dry coater manufactured by Hitachi, Ltd., and a vacuum laminator manufactured by Showa Denko Materials Electronics Co., Ltd.
[0260] When a protective film is provided on the photosensitive resin film, after peeling or removing the protective film, the photosensitive resin film can be laminated by being pressed and bonded to the circuit board while being pressed and heated in a state where the photosensitive resin film is in contact with the circuit board.
[0261] The lamination can be performed, for example, after preheating the photosensitive resin film and the circuit board as needed, at a pressure-bonding temperature of 70 to 130° C., a pressure-bonding pressure of 0.1 to 1.0 MPa, and an air pressure of less than or equal to 20 mmHg (26.7 hPa), but is not particularly limited to these conditions. In addition, the lamination method can be intermittent or continuous using a roller.
[0262] Finally, the photosensitive resin film laminated on the circuit board is cooled to near room temperature to form the interlayer insulating layer 103. When the photosensitive resin film has a carrier film, the carrier film may be peeled off at this time or after exposure as described later.
[0263] (Optical through hole forming step (2))
[0264] In the optical through hole forming step (2), at least a portion of the photosensitive resin film laminated on the circuit substrate is exposed and then developed. By exposure, the portion irradiated by the active light is photocured to form a pattern. The exposure method is not particularly limited. For example, a method of irradiating the active light in an image-like manner through a negative or positive mask pattern called an artwork (mask exposure method) can be adopted, or a method of irradiating the active light in an image-like manner through a direct drawing exposure method such as LDI (Laser Direct Imaging) exposure method, DLP (Digital Light Processing) exposure method, etc. can be adopted.
[0265] As the light source of the active light, a known light source can be used. Specifically, as the light source, gas lasers such as carbon arc lamps, mercury vapor arc lamps, high-pressure mercury lamps, xenon lamps, and argon lasers; solid lasers such as YAG lasers; and light sources such as semiconductor lasers that effectively radiate ultraviolet light or visible light. The exposure amount can be appropriately selected according to the light source used and the thickness of the photosensitive layer. For example, in the case of ultraviolet irradiation from a high-pressure mercury lamp, when the thickness of the photosensitive layer is 1 to 100 μm, 10 to 1,000 mJ / cm is usually preferred. 2 More preferably, it is 50 to 700 mJ / cm 2 , and more preferably 150 to 550 mJ / cm 2 , particularly preferably 250 to 500 mJ / cm 2 .
[0266] In the development, the uncured portion of the photosensitive layer is removed from the substrate, so that the photocured portion is formed as an interlayer insulating layer on the substrate.
[0267] When there is a carrier film on the photosensitive layer, after removing the carrier film, the unexposed portion is removed (developed). There are two developing methods: wet development and dry development. Either method can be used, but wet development is widely used. In this embodiment, wet development can also be used.
[0268] In the case of wet development, a developer corresponding to the photosensitive resin composition is used to develop by a known development method. As the development method, there can be cited methods using immersion, spinning immersion, spraying, brushing, slapping, scraping, shaking immersion, etc. Among them, from the viewpoint of improving the resolution of the through hole, the spray method is preferred, and the high-pressure spray method is more preferred among the spray methods. Development can be implemented by one method or by combining two or more methods.
[0269] The structure of the developer can be appropriately selected according to the structure of the photosensitive resin composition, and examples thereof include alkaline aqueous solutions, water-based developers, and organic solvent-based developers, among which alkaline aqueous solutions are preferred.
[0270] In the optical through hole forming step (2), after exposure and development, 0.2 to 10 J / cm 2 About (preferably 0.5 to 5 J / cm 2 ) and post-heat curing at a temperature of about 60 to 250° C. (preferably 120 to 200° C.), thereby further curing the interlayer insulating layer, and it is preferred to further cure it.
[0271] By the above method, an interlayer insulating layer having a through hole 104 is formed. The shape of the through hole is not particularly limited. If the cross-sectional shape is described, a quadrilateral, an inverted trapezoid (the upper side is longer than the lower side), etc. can be listed. If the shape is described from the front (the direction in which the bottom of the through hole can be seen), a circle, a quadrilateral, etc. can be listed. In the formation of the through hole based on the photolithography method in this embodiment, a through hole with a cross-sectional shape of an inverted trapezoid (the upper side is longer than the lower side) can be formed. In this case, the coverage (returnability) of the copper plating layer to the through hole wall surface becomes higher, so it is preferred.
[0272] The size (diameter) of the through hole 104 formed by this process can be set to be less than 40 μm, and can also be set to be less than or equal to 35 μm or less than or equal to 30 μm, which can be smaller than the size of the through hole made by laser processing. The lower limit of the size (diameter) of the through hole formed by this process is not particularly limited, and can be greater than or equal to 15 μm, or greater than or equal to 20 μm.
[0273] However, the size (diameter) of the through hole 104 formed in this step is not limited to less than 40 μm, and may be arbitrarily selected within the range of 15 to 300 μm, for example.
[0274] (Roughening process (3))
[0275] As required, as a roughening treatment step (3), a roughening liquid is used to perform a roughening treatment on the surface of the through hole and the interlayer insulating layer. In addition, in the case where smear is generated in the above-mentioned optical through hole forming step (2), the smear can also be removed by the above-mentioned roughening liquid. The roughening treatment and the removal of smear (smear removal) can be performed simultaneously.
[0276] Examples of the roughening liquid include a chromium / sulfuric acid roughening liquid, an alkaline permanganate roughening liquid (for example, a sodium permanganate roughening liquid), and a sodium fluoride / chromium / sulfuric acid roughening liquid.
[0277] Through the roughening process, concave and convex anchor points are formed on the surface of the through hole and the interlayer insulating layer.
[0278] (Circuit pattern forming step (4))
[0279] The circuit pattern forming step (4) is a step of forming a circuit pattern on the interlayer insulating layer after the roughening step (3).
[0280] From the viewpoint of forming fine wiring, the formation of the circuit pattern is preferably performed by a semi-additive process. By the semi-additive process, the circuit pattern is formed and the through-hole is connected at the same time.
[0281] In the semi-additive process, first, a palladium catalyst is used on the bottom of the through hole, the wall of the through hole and the entire surface of the interlayer insulating layer after the above-mentioned roughening treatment step (3), and then a chemical copper plating treatment is performed on this basis to form a seed layer 105. The seed layer 105 is used to form a power supply layer for electroplating copper, and is preferably formed with a thickness of about 0.1 to 2.0 μm. If the thickness of the seed layer 105 is greater than or equal to 0.1 μm, there is a tendency to suppress the reduction of connection reliability during electroplating copper. If it is less than or equal to 2.0 μm, there is no need to increase the etching amount when flash etching the seed layer between the wirings, and there is a tendency to suppress the damage to the wiring caused by etching.
[0282] The chemical copper plating treatment is performed by the reaction of copper ions and a reducing agent to precipitate metal copper on the surface of the through hole and the interlayer insulating layer.
[0283] The chemical plating method and the electroplating method may be any known method and are not particularly limited.
[0284] As the chemical copper plating solution, a commercially available product may be used, and examples of the commercially available product include "MSK-DK" manufactured by Atotech Japan Co., Ltd. and "Thru-cup (registered trademark) PEA series" manufactured by Uemura Industries Co., Ltd.
[0285] After the chemical copper plating treatment, a dry film resist is thermally pressed onto the chemical copper plating layer using a roll laminator. The thickness of the dry film resist must be higher than the wiring height after the copper electroplating. From this point of view, a dry film resist with a thickness of 5 to 30 μm is preferred. As a dry film resist, the "PHOTEC (registered trademark)" series manufactured by Showa Denko Materials Co., Ltd. is used.
[0286] After the dry film resist is thermocompressed, for example, the dry film resist is exposed through a mask having a desired wiring pattern. The exposure can be performed using the same device and light source as those used to form a through hole on the photosensitive resin film. After the exposure, the dry film resist is developed using an alkaline aqueous solution to remove the unexposed portion, thereby forming a resist pattern 106. Thereafter, the development residue of the dry film resist may be removed using plasma or the like as needed.
[0287] After development, copper electroplating is performed to form a copper circuit layer (circuit pattern) 107 and fill the through-holes.
[0288] After copper electroplating, the dry film resist is stripped using an alkaline aqueous solution or an amine stripper. After stripping the dry film resist, the seed layer between the wirings is removed (flash etching). Flash etching is performed using an acidic solution such as sulfuric acid and hydrogen peroxide and an oxidizing solution. After flash etching, palladium and the like attached to the portion between the wirings are removed as needed. The removal of palladium can preferably be performed using an acidic solution such as nitric acid and hydrochloric acid.
[0289] After the stripping of the above-mentioned dry film resist or after the flash etching process, a post-baking treatment is preferably performed. The post-baking treatment can fully thermally cure the unreacted thermosetting components, thereby tending to improve the insulation reliability, curing characteristics and bonding strength with the copper plating layer. The thermal curing conditions vary depending on the type of resin composition, etc., and the preferred curing temperature is 150 to 240°C and the curing time is 15 to 100 minutes. Through the post-baking treatment, the entire manufacturing process of the multilayer printed wiring board 100A using the optical through-hole method is completed, and the substrate is manufactured by repeatedly performing this process according to the required number of interlayer insulation layers. In addition, a solder resist layer 108 is preferably formed on the outermost layer.
[0290] The above is a description of a method for manufacturing a multilayer printed wiring board in which a through hole is formed using the photosensitive resin composition of the present embodiment. The photosensitive resin composition of the present embodiment is excellent in pattern resolution, and therefore is also suitable for forming a cavity for a built-in chip or a passive component, etc. For example, in the description of the multilayer printed wiring board described above, the cavity can be appropriately formed by exposing the photosensitive resin film to form a pattern so that the pattern is formed as a desired cavity. In addition, the photosensitive resin composition of the present embodiment is also useful as a solder resist.
[0291] [Semiconductor packaging]
[0292] The present disclosure also provides a semiconductor package including the multilayer printed wiring board of the present embodiment and a semiconductor element. The semiconductor package of the present embodiment can be manufactured by mounting a semiconductor element such as a semiconductor chip or a memory on a predetermined position of the multilayer printed wiring board of the present embodiment and then sealing the semiconductor element with a sealing resin or the like.
[0293] Example
[0294] Hereinafter, the present embodiment will be described in more detail by way of examples, but the present disclosure is not limited to these examples. It should be noted that the acid value and weight average molecular weight of component (A) are measured by the following method, and the true density of component (X), component (X') and component (E) are measured by the following method. In addition, the properties of the photosensitive resin composition obtained in each example are evaluated by the method shown below.
[0295] <Method for measuring acid value>
[0296] The acid value of the component (A) is calculated from the amount of the potassium hydroxide aqueous solution required to neutralize the component (A).
[0297] <Method for measuring weight average molecular weight>
[0298] The weight average molecular weight of component (A) was measured by the following GPC measuring device and measuring conditions, and the value converted using the calibration curve of standard polystyrene was used as the weight average molecular weight. In addition, in the preparation of the calibration curve, 5 sample groups ("PStQuick MP-H" and "PStQuick B", manufactured by Tosoh Corporation) were used as standard polystyrene.
[0299] (GPC measurement device)
[0300] Equipment: High-speed GPC equipment "HCL-8320GPC", detector is differential refractometer or UV, manufactured by Tosoh Corporation
[0301] Column: Column TSKgel SuperMultipore HZ-H (column length: 15cm, column inner diameter: 4.6mm), manufactured by Tosoh Corporation
[0302] (Measurement conditions)
[0303] Solvent: Tetrahydrofuran (THF)
[0304] Measurement temperature: 40℃
[0305] Flow rate: 0.35ml / min
[0306] Sample concentration: 10mg / THF 5ml
[0307] Injection volume: 20μl
[0308] <Method for measuring true density and calculating hollow ratio>
[0309] (True density)
[0310] First, component (X) or component (X') is placed in a mortar and ground with a pestle to obtain component (X) or component (X') having a particle size of 0.1 μm or less. The particle size of the component (X) or component (X') is measured using a dry automatic density meter "AccuPycII 1340" (manufactured by Shimadzu Corporation) at 1 cm 3 The sample cell is filled with the ground component (X) or component (X') to 80%. The weight of the sample cell filled with the above component is measured, and the weight of the component filled in the sample cell is subtracted from the weight of the sample cell alone to obtain the weight of the component filled in the sample cell.
[0311] Next, a sample cell filled with the above-mentioned component is set in the above-mentioned dry automatic density meter, and the weight of the component is input. After being placed at room temperature and in a nitrogen atmosphere for 1 hour with the sample cell set, 10 measurements are performed to obtain the average value. The average value is taken as the true density.
[0312] (Hollowness)
[0313] In addition to the above-mentioned true density measurement, the apparent density (specific gravity) of the component (X) or the component (X') is measured by the above-mentioned dry automatic density meter. The apparent density (specific gravity) is measured as follows. The 1 cm diameter of the dry automatic density meter "AccuPycII1340" (manufactured by Shimadzu Corporation) is used to measure the apparent density (specific gravity). 3 Fill the sample cell with component (X) or component (X') (both are not ground but in their original state) until 80%. Measure the weight of the sample cell filled with the above components, and subtract the weight of the sample cell alone to find the weight of the component filled in the sample cell. Next, set the sample cell filled with the above components in the above-mentioned dry automatic density meter, and input the weight of the component. After leaving the sample cell at room temperature and nitrogen atmosphere for 1 hour, perform 10 measurements and find the average value. The average value is taken as the apparent density (specific gravity).
[0314] The hollow ratio was calculated according to the following formula using the apparent density (specific gravity) obtained as described above and the true density.
[0315] Hollowness (%) = 100 × {1-(apparent density) / (true density)}
[0316] [1. Evaluation of relative dielectric constant (Dk)]
[0317] Two photosensitive resin films with the protective films peeled off were laminated together and irradiated with 2 J / cm2 using a UV conveyor exposure machine with carrier films on both sides. 2 (wavelength: 365 nm) The sample was heat-treated at 170° C. for 1 hour in a hot air circulation dryer and cut into a size of 7 cm×10 cm. The sample obtained was used as an evaluation sample.
[0318] The obtained evaluation sample was dried at 105° C. for 10 minutes using a hot air circulation dryer, and then the relative dielectric constant (Dk) was measured in a 10 GHz frequency band by a separated column dielectric resonator method (SPDR method).
[0319] [2. Evaluation of bonding strength with copper plating and evaluation of the presence or absence of plating peeling]
[0320] While peeling off the protective film from the "photosensitive resin film bonded with a carrier film and a protective film" manufactured in each embodiment and comparative example, a pressurized vacuum laminator (manufactured by Meiki Manufacturing Co., Ltd., trade name "MVLP-500") was used to laminate on a copper-clad laminate substrate with a thickness of 1.0 mm under the conditions of a crimping pressure of 0.4 MPa, a pressurized hot plate temperature of 80°C, a vacuuming time of 25 seconds, a lamination pressurizing time of 25 seconds, and an air pressure of less than or equal to 4 kPa to obtain a laminate.
[0321] The obtained laminate was exposed to light at 400 mJ / cm using a parallel light exposure machine (manufactured by ORC Manufacturing Co., Ltd., trade name "EXM-1201") using an ultra-high pressure mercury lamp as a light source. 2 The entire surface was exposed with a UV exposure device at 2,000 mJ / cm 2 After exposure with an exposure amount of 1:1 (wavelength: 365 nm), the film was heated at 170° C. for 1 hour to obtain an “evaluation laminate” in which a cured product was formed on the copper-clad laminate substrate.
[0322] Next, first, an aqueous solution of "200 ml / L of diethylene glycol monobutyl ether and 5 g / L of sodium hydroxide" was prepared as a swelling solution, and then heated to 70°C, and then the evaluation laminate was immersed for 10 minutes. Next, as a roughening solution, an aqueous solution of 60 g / L of potassium permanganate and 40 g / L of sodium hydroxide was prepared, and then heated to 70°C, and then the evaluation laminate was immersed for 15 minutes. Next, an aqueous solution of a neutralizing solution (30 g / L of tin chloride (SnCl2), 300 ml / L of hydrogen chloride) was prepared, and then heated to 40°C, and then the evaluation laminate was immersed for 5 minutes to reduce the potassium permanganate. As described above, the surface of the cured product of the evaluation laminate was desmeared.
[0323] Next, the surface of the cured product of the evaluation laminate treated with desmear was treated with an alkaline cleaning liquid "Cleaner Securiganth 902" (manufactured by ATOTECH JAPAN Co., Ltd., trade name) at 60°C for 5 minutes, and then degreased and cleaned. After cleaning, the cured product treated with desmear was treated with a pre-dip liquid "Pre Dip Neoganth B" (manufactured by ATOTECH JAPAN Co., Ltd., trade name) at 23°C for 1 minute. Then, the cured product was treated with an activating liquid "Activator Neoganth 834" (manufactured by ATOTECH JAPAN Co., Ltd., trade name) at 35°C for 5 minutes, and then treated with a reducing liquid "Reducer Neoganth WA" (manufactured by ATOTECH JAPAN Co., Ltd., trade name) at 30°C for 5 minutes.
[0324] The evaluation laminate thus obtained was placed in a chemical copper solution ("Basic Printoganth MSK-DK", "Copper Printoganth MSK", "Stabilizer Printoganth MSK" (all manufactured by ATOTECH JAPAN Co., Ltd., trade names)) and subjected to chemical plating until the plating thickness reached about 0.5 μm. After the chemical plating, an annealing treatment was performed at a temperature of 120° C. for 30 minutes in order to remove the residual hydrogen. Then, copper sulfate electroplating was performed and an annealing treatment was performed at 180° C. for 60 minutes to form a conductor layer with a thickness of 25 μm.
[0325] The vertical peel strength of the laminate for evaluation having the conductor layer formed as described above was measured at 23° C. in accordance with JIS C6481 (1996), and was evaluated according to the following evaluation criteria.
[0326] A: The bonding strength to the copper plating layer is greater than or equal to 0.4 kN / m.
[0327] B: The bonding strength to the copper plating layer is greater than or equal to 0.3 kN / m and less than 0.4 kN / m.
[0328] C: The bonding strength to the copper plating layer is greater than 0.1 kN / m and less than 0.3 kN / m.
[0329] D: The bonding strength to the copper plating layer is less than or equal to 0.1 kN / m.
[0330] In addition, the surface of the evaluation laminate after the annealing treatment was visually observed to confirm whether the plating peeled off. If the plating peeled off, the plating surface was uneven, and if the plating peeled off, the plating surface was flat.
[0331] [Preparation of photosensitive resin composition]
[0332] Examples 1 to 5, Comparative Examples 1 to 3
[0333] (1) Production of photosensitive resin composition
[0334] The composition was prepared according to the composition shown in Table 1 (the unit of the numerical values in the table is parts by mass, and in the case of a solution, it is the amount of solid content conversion), and then kneaded using a three-roll mill. Then, methyl ethyl ketone was added to make the solid content concentration 65% by mass to obtain a photosensitive resin composition.
[0335] (2) Production of photosensitive resin film
[0336] A polyethylene terephthalate film (manufactured by Teijin Limited, trade name "G2-16") having a thickness of 16 μm was used as a carrier film. The photosensitive resin composition prepared in each example was coated on the carrier film, and the film thickness after drying was adjusted to 25 μm, and dried at 100° C. for 10 minutes using a hot air convection dryer to form a photosensitive resin film (photosensitive layer).
[0337] Next, a polyethylene film (manufactured by TAMAPOLY CORPORATION, trade name "NF-15") was laminated as a protective film on the surface of the photosensitive resin film (photosensitive layer) opposite to the surface in contact with the carrier film, thereby preparing a photosensitive resin film laminated with the carrier film and the protective film.
[0338] The results are shown in Table 1.
[0339] [Table 1]
[0340]
[0341] The unit of content is part by mass, which corresponds to the amount based on solid content in the case of a solution or dispersion.
[0342] The content in parentheses is "volume %" based on the total solid content.
[0343] The components used in Table 1 are as follows.
[0344] [(A) Photopolymerizable Compound Having Ethylenically Unsaturated Group and Acidic Substituent]
[0345] ·A1: "ZXR-1935H" (manufactured by Nippon Kayaku Co., Ltd., acid value: 110 mgKOH / g, weight average molecular weight: 2,000)
[0346] [(B) Thermosetting resin]
[0347] B1: "EPOTOHTO (registered trademark) ESN-475V" (manufactured by Nippon Steel Chemical Materials Co., Ltd., naphthol-type epoxy resin, epoxy equivalent: 325 g / eq)
[0348] B2: "NC-3000L" (manufactured by Nippon Kayaku Co., Ltd., biphenyl aralkyl type epoxy resin, epoxy equivalent: 272 g / eq)
[0349] [(C) Cross-linking agent]
[0350] C1: “TMPTA” (trimethylolpropane triacrylate)
[0351] [(D) Elastomer]
[0352] D1: "Ricon (registered trademark) 131MA17" (manufactured by Cray Valley, maleic acid-modified polybutadiene, number average molecular weight 54,000 (catalog value))
[0353] D2: "Ricon (registered trademark) 100" (manufactured by Cray Valley, butadiene-styrene random copolymer, number average molecular weight 45,000 (catalog value))
[0354] [(X) as true density less than or equal to 1,500 kg / m 3 Solid particles of inorganic filler materials]
[0355] X1: True density is 1,350 kg / m 3 Solid particles of spherical fused silica (volume average particle size: 0.7 μm) treated with a silane coupling agent, hollow ratio = 39%
[0356] X2: True density is 1,350 kg / m 3 Solid particles of spherical fused silica (volume average particle size: 1.5 μm) treated with a silane coupling agent, hollow ratio = 39%
[0357] X3: True density is 1,350 kg / m 3 Solid particles of spherical fused silica (volume average particle size: 3.0 μm) treated with a silane coupling agent, hollow ratio = 39%
[0358] [(X') Inorganic filler other than the above-mentioned component (X)]
[0359] (As true density greater than 1,500kg / m 3 Solid particles of inorganic filler materials)
[0360] ·X'1: True density is 2,210kg / m 3 Solid particles of spherical fused silica (volume average particle size: 0.5 μm) treated with a silane coupling agent, hollow ratio = 0%
[0361] (As true density less than or equal to 1,500kg / m 3 Inorganic filling material of hollow particles)
[0362] ·X'2: True density is 620kg / m 3 Hollow particles of spherical fused silica (volume average particle size: 0.7 μm) treated with a silane coupling agent, hollow ratio = 72%
[0363] [(E) Organic filler]
[0364] PTFE: "M-7226EX" (Made by Morimura Chemical Co., Ltd., volume average particle size: 200 nm)
[0365] [(F) Curing agent]
[0366] F1: "Phenolite (registered trademark) LA7052" (manufactured by DIC Corporation, a novolac-type phenolic resin modified with melamine, benzoguanamine, etc., hydroxyl equivalent: 120 g / eq)
[0367] [(G) Curing accelerator]
[0368] ·G1: 2-phenyl-1-benzyl-1H-imidazole (imidazole compound)
[0369] [(H) Photopolymerization initiator]
[0370] H1: 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetoxime) (oxime ester compound)
[0371] H2: Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (acylphosphine oxide compound)
[0372] [(I) Photosensitizer]
[0373] ·I1: 4,4'-Bis(diethylamino)benzophenone
[0374] [(J) Additives]
[0375] ·4-tert-butylcatechol; polymerization inhibitor
[0376] · "SH-193" (manufactured by Dow-Toray Co., Ltd., silicone foam stabilizer)
[0377] As shown in Table 1, the photosensitive resin compositions of Examples 1 to 5 of the present embodiment have a true density of 2,210 kg / m 3 Compared with the photosensitive resin composition of Comparative Example 1 of the inorganic filler containing 2,4-dimethyl-1,2-dioxane, ...
[0378] It is understood that the photosensitive resin composition of Comparative Example 2, which contains a large amount of PTFE for the purpose of significantly reducing the relative dielectric constant, achieves the purpose, but the bonding strength with the copper plating layer is significantly reduced, and the plating layer is easily peeled off.
[0379] In addition, even if the true density is less than or equal to 1,500 kg / m 3 In the case of hollow particles, the bonding strength with the copper plating layer was also greatly reduced, and plating peeling occurred.
[0380] Description of Reference Numerals
[0381] 100A Multilayer Printed Wiring Board
[0382] 101 substrate
[0383] 102 Circuit Pattern
[0384] 103 interlayer insulation layer
[0385] 104 Through hole (conducting hole)
[0386] 105 Seed Layer
[0387] 106 Resist pattern
[0388] 107 Copper circuit layer
[0389] 108 Solder mask.
Claims
1. A photosensitive resin composition comprising (X) as a true density of less than or equal to 1,500 kg / m 3 Inorganic filling material with solid particles. 2 . The photosensitive resin composition according to claim 1 , wherein the component (X) has a volume average particle size of 0.3 to 3 μm. 3 . The photosensitive resin composition according to claim 1 , wherein the content of the component (X) is 1 to 45% by volume based on the total solid content of the photosensitive resin composition. 4 . 4 . The photosensitive resin composition according to claim 1 , further comprising (A) a photopolymerizable compound having an ethylenically unsaturated group and an acidic substituent and (B) a thermosetting resin.
5. The photosensitive resin composition according to claim 4, wherein the component (A) comprises an alicyclic skeleton represented by the following general formula (A-1): [Chemistry 1] In the formula, R A1 represents an alkyl group having 1 to 12 carbon atoms, which may be substituted at any position of the alicyclic skeleton, and m 1 is an integer of 0 to 6, and * is a bonding site with other structures. 6 . The photosensitive resin composition according to claim 4 , wherein the equivalent ratio of the acidic substituent of the component (A) to the epoxy group of the component (B), that is, epoxy group / acidic substituent, is 0.5 to 6.
0. 7 . The photosensitive resin composition according to claim 1 , further comprising (C) a crosslinking agent. 8 . The photosensitive resin composition according to claim 1 , further comprising (D) an elastomer. 9 . The photosensitive resin composition according to claim 1 , further comprising (E) an organic filler. 10 . The photosensitive resin composition according to claim 9 , wherein the component (E) comprises resin particles composed of at least one selected from the group consisting of resins having fluorine atoms, polyethylene, polypropylene, polystyrene, polyphenylene ether, and silicone. 11 . The photosensitive resin composition according to claim 9 , wherein the content of the component (E) is 1 to 45% by volume based on the total solid content of the photosensitive resin composition. 12 . The photosensitive resin composition according to claim 1 , further comprising (H) a photopolymerization initiator. 13 . The photosensitive resin composition according to claim 12 , comprising two or more types of the component (H). 14 . A photosensitive resin composition for forming an optical via hole, comprising the photosensitive resin composition according to claim 1 . 15 . A photosensitive resin film formed using the photosensitive resin composition according to claim 1 . 16 . A multilayer printed wiring board comprising an interlayer insulating layer formed using the photosensitive resin composition according to claim 1 or the photosensitive resin film according to claim 15 .
17. A semiconductor package comprising the multilayer printed wiring board according to claim 16, and a semiconductor element.
18. A method for manufacturing a multilayer printed wiring board, comprising the following (1), (2) and (4): (1) Laminating the photosensitive resin film according to claim 15 on one or both sides of a circuit substrate; (2): exposing and developing the photosensitive resin film laminated in (1) to form an interlayer insulating layer having a through hole; as well as (4): A circuit pattern is formed on the interlayer insulating layer.
Citation Information
Cited By
Alkali-soluble resin, preparation method thereof and photosensitive dry film resist
CN121343052A
An alkali-soluble resin, a method for producing the same, and a photosensitive dry film resist
CN121343052B
